Effectiveness of Trichoderma atroviride biopriming on germination of chili pepper seeds infected with Colletotrichum and Fusarium - Ayumi Rizci Puspita; Feskaharny Alamsjah; Anthoni Agustien; Suwirmen Suwirmen; Mellanie Alia Putri (Universitas Djuanda, 2026)
Seed-borne diseases caused by Colletotrichum and Fusarium can reduce the viability and vigor of chili seeds. An environmentally friendly alternative for disease management is the use of Trichoderma atroviride as a biopriming agent. This study aimed to evaluate the effectiveness of T. atroviride biopriming on the germination of Kopay chili seeds infected with Colletotrichum scovillei and Fusarium oxysporum. The experiment was arranged in a Completely Randomized Design (CRD) consisting of eight treatments with four replications. Observed parameters included germination percentage, root length, shoot length, fresh weight, dry weight, vigor index, and root emergence time. Data were analyzed using analysis of variance (ANOVA) followed by Duncan’s New Multiple Range Test (DNMRT) at the 5% significance level. The results showed that T. atroviride treatment produced the highest germination percentage (100%), which was not significantly different from the positive control (95%) and negative control (90%). The T. atroviride treatment also resulted in the greatest root length (2.54 cm), shoot length (1.74 cm), highest vigor index (100%), and the fastest root emergence (2 days). In contrast, the C. scovillei treatment exhibited the lowest germination percentage (30%) and vigor index (45%). These findings suggest that biopriming with T. atroviride has the potential to enhance seed vigor and support early seedling growth of chili under seed-borne pathogen stress.